1969
DOI: 10.1111/j.1365-2621.1969.tb00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of Trichina Larvae in Cooked Pork Roasts

Abstract: SUMMARY–The effect of heat on trichina larvae was studied in pork roasts cut from trichinae infected loins. Roasts were cooked to end‐point temperatures of 120, 125, 130, 135, 140, 145, 150 or 160°F in electric household ranges at oven temperatures of 200, 325 or 350°F. Samples of the cooked roasts were artificially digested; the recovered‐ larvae were examined for viability. Also samples were fed to rats; 4 weeks later the rats were killed and examined for presence of trichinae by digesting aliquots of ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

1981
1981
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 3 publications
(2 reference statements)
0
10
0
2
Order By: Relevance
“…Also, Trichinellu spirulis is reported (USDA 1960;Carlin et al 1969) to be completely destroyed at temperatures of about 58C. Cooking methods are known to affect the content and retention of many nutrients in foods.…”
Section: Introductionmentioning
confidence: 98%
“…Also, Trichinellu spirulis is reported (USDA 1960;Carlin et al 1969) to be completely destroyed at temperatures of about 58C. Cooking methods are known to affect the content and retention of many nutrients in foods.…”
Section: Introductionmentioning
confidence: 98%
“…The unevenness of heat distribution during microwave cooking is probably the primary reason for the problem, although the relatively short exposure to heat when compared to that for conventional cooking methods also may be a factor. Although 58.3'~ is confirmed as a safe level to devitalize trichinae in conventionally cooked pork (Ransom and Schwartz, 1919;Otto and Abrams, 1939;and Carlin et al, 1969), Zimmermann (1983a) found infective trichinae in five well done, microwave-cooked pork roasts and speculated that the 58.3'C standard may not always be valid for microwave cooked products. Howe et al (1982) found that pinkness was evident in pork roasts cooked in a conventional oven to 50 or 60°C but not when cooked to 70 or 8O'C.…”
Section: Studies By Zimmermann and Beachmentioning
confidence: 95%
“…In uno studio sulla distruzione termica delle larve di trichina in arrosti di maiale, tutti gli arrosti cotti fino a una temperatura interna di almeno 140°F (60°C) risultavano liberi dal parassita 11 ; le larve erano invece ancora presenti in tutti gli arrosti che raggiungevano temperature pari o inferiori a 130°F (54,4°C) e in alcuni arrosti cotti a 135°F. L'alimentazione dei suini con scarti di alimenti crudi favorisce la perpetuazione della malattia; nelle zone in cui ai maiali vengono somministrati solo scarti cotti si osserva una drastica riduzione dell'incidenza della trichinellosi.…”
Section: Prevenzione E Controllounclassified
“…Trichine vive furono ritrovate sia nei prosciutti che nelle spalle 3 settimane dopo l'affumicatura, mentre non ne furono ritrovate dopo 4 settimane. È stato dimostrato che, per le larve di trichina presenti in un arrosto, la cottura è più distruttiva quando il calore viene fornito lentamente in un forno tradizionale fino a raggiungere 200°F (93,3°C) rispetto a quando viene fornito rapidamente fino a raggiungere 350°F o 176,7°C 11 . Carne ottenuta da maiali infettati sperimentalmente fu usata per preparare i salami.…”
Section: Prevenzione E Controllounclassified